Analisis Faktor Determinan Pengaliran Air Bersih untuk Pembangunan Ekonomi Daerah di Pulau Jawa Berbasis Green Economy - Tedjosukmono, Gabriele Natasha; Pratomo, Gigih (Economie: Jurnal Ilmu Ekonomi, 2025)
Clean water, as one of a living creature’s main resources to live, is supposedly considered as one of renewable resources available on Earth that is accessible to everyone and plays a huge role in our daily lives. In spite of clean water being everywhere on Earth, as time goes on, with the growing population rate, the increasing rate of pollution, and many other factors, the water that is available on Earth is no longer ethical to be used daily since those degradation factors mentioned are implying water scarcity in the future. This has led us into irony. Water, which is supposedly one of renewable resources, will no longer safe to be accessed by everyone. This study used quantitative methodologies and a fixed effect model approach to perform research utilizing panel type data. According to the analysis performed for this study, the number of consumers, employees, and businesses that are present and dispersed over Java Island has a 96% influence on the amount of water given to the community.